Surface Charge Accumulation on Basin-Shape Insulator in Various Eco-Friendly Gases with Metal Particle Under AC Voltage - Xiaohui Duan; Chuanyun Zhu; Qifeng Shang; Zhen Zhang; Kaiyuan Wang; Yu Gao (Energies)
Surface charge accumulation is considered one of the key factors that lead to unexpected insulator flashover failures in gas-insulated switchgear (GIS). With the existence of metal particles, charge accumulation characteristics on insulator surfaces become intricate in eco-friendly gases under AC voltage. In this study, the surface charge behavior on a down-scaled 252 kV AC GIS basin insulator model with a linear metal particle adhered to the HV electrode on the convex surface in compressed air (80%N2/20%O2) and C4F7N/CO2 mixtures was investigated. After applying an AC voltage of 40 kV for 5 min, the charge densities on both surfaces were measured, and the effect of the metal particle and gas parameters was discussed. The results showed that charge spots were induced by metal particles on the insulator surfaces, and the polarities of which varied with the gas atmosphere. A decrease in maximum charge density was detected with an increase in C4F7N proportion at 0.1 MPa, and soar of which was observed at 0.5 MPa. With an increase in gas pressure, the maximum charge density increased in both atmospheres. The total quantity of charges showed similar behavior to the charge densities. It is indicated that the high electronegativity of C4F7N molecules presents a competing relationship in charge accumulation as the pressure increases.